Why Does Removing Machines Count as “Passive” Euthanasia? - Hopkins, Patrick D. (The Hastings Center report, 1997)
The distinction between “passive” and “active” euthanasia, though problematic and highly criticized, retains a certain intuitive appeal. When a patient is allowed to die, nature appears simply to be taking its course. Yet when a patient is killed by, say, a lethal injection, humans appear to be causing his or her death. Guilt seems to follow naturally from the latter act while not from the former. Yet this view only holds up if age-old and vague ideasabout “nature” and “artifice” go unscrutinized. Once examined more closely the functional relevance of particular machines to particular bodies becomes evident. And the innocence and guilt less clear.